Postmoderne Bybelwetenskap en die Christelike godsdiens – kanttekeninge by die boek Geloof sonder sekerhede: Besinning vir eietydse gelowiges - Spangenberg, IJJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
At the end of 2005 Anton van Niekerk, a philosopher from the University of Stellenbosch, published a book with the title Geloof sonder sekerhede: Besinning vir eietydse gelowiges (= Belief without absolutes: Reflections for contemporary believers). According to him, believers can no longer be expected to adhere to outdated doctrines like original sin and the virginal conception. Our world-view differs radically from previous generations’ world-views. However, he does not want to sever his ties with the Christian tradition. He criticizes those biblical scholars in South Africa who advocate a new reformation since they (according to him) sever their ties with the tradition. In his view Christians should rather focus on ethics than on doctrines. Although the book contributes to the discussion of ethical issues in our context (AIDS, poverty, medical research, etc) the author seems unaware of the current state of biblical research. This seriously undermines his contribution to the theological debates in South Africa.